Evaluation of the treatment of patients with distal tibial fractures treated by anatomical plate - سعد, معن (Latakia University Journal -Medical Sciences Series, 2024)
Objective : to evaluate the clinical and functional results of patients with Extra-articular tibia fractures treated by using the anatomical plate . Materials and methods : this study included 23 patients from the reviewers of Tishreen University Hospital in Lattakia between 2021-2022 . All patients in this study underwent correction of fractures of Extra-articular tibia fractures using the anatomical plate after appropriate clinical and Radiological evaluation . Rehabilitation was recommended for all patients after surgery and patients have been followed up at maximum intervals after 12 months of treatment . Results: The study sample consisted of 23 patients with a predominance of males by more than 62% . The majority of patients participating in the study were within the age group between 36-55 years with 52%. Complications occurred within 6 of the patients in the study sample by 26% and varied between Complex Regional pain Syndrome (Sudeck's Dystrophy ), superficial infection (8,7%), and superficial caries (4,34%) while not recording any other complications in patients undergoing anatomical plates . The values of the AOFAS index were excellent in the majority of cases with a percentage of 43.56%. Conclusion: this study showed the positive results of the treatment of Extra-articular tibia fractures using the anatomical plate, the importance of this surgical technique in the management of these cases, and its positive impact on rehabilitation.